Peran Corporate Social Responsibility (CSR) Dalam Meningkatkan Reputasi Dan Keberlanjutan Bisnis Di Era Modern - Aisyah, Siti (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to analyze the role of Corporate Social Responsibility (CSR) in enhancing corporate reputation and supporting business sustainability in the modern era, which is marked by increasing public awareness of social and environmental responsibilities. CSR is no longer viewed merely as philanthropic activity, but rather as an integral part of a sustainable business strategy. The research employs a descriptive qualitative approach using case study techniques on several companies actively implementing CSR programs in Indonesia. Data were collected through in-depth interviews, documentation, and literature review, then analyzed thematically to identify the relationship between CSR implementation and corporate reputation, as well as key indicators of business sustainability such as customer loyalty, public trust, and operational efficiency. The results show that CSR, when integrated into business strategy, can significantly enhance corporate reputation. Sustainable CSR programs that are responsive to community needs also contribute to fostering harmonious relationships with stakeholders, improving corporate image, and supporting long-term business stability and growth. Thus, CSR proves to be not only socially and environmentally beneficial but also strategically valuable for the survival of companies in the modern era.